XXX Meeting of the Brazilian Society of Acoustics - Araújo, Bianca; Araújo, Virgínia (Acústica e Vibrações, 2023)
Between November 19 and 22, 2023, the XXX Meeting of the Brazilian Society of Acoustics (Sobrac) took place at the UFRN Engineering Technology Center in Natal, Brazil. This event, which marks Sobrac's 40th anniversary, is the largest and only technical-scientific meeting in Brazil focused on acoustics and vibrations. Bringing together 292 participants, the event featured the presentation of 68 papers in 18 thematic areas, as well as five lectures, six short courses, two round tables, and a workshop, with an outstanding international presence. There was also an exhibition fair with 22 exhibitors and two technical visits, which attracted around 250 professionals each day. The event ended with the awarding of seven prizes in a student competition. The final evaluation by the participants highlighted the high level of organization and technical-scientific level of the meeting.